The Effectiveness of TOEFL Program on the Students' English Proficiency: A Case of an Indonesian University - Ahmad Amin Dalimunte; Chanata Somanawattana; Deasy Yunita Siregar (JEELS (Journal of English Education and Linguistics Studies), 2025)
Having sufficient English language ability is considered important for university students to begin their undergraduate studies. English serves as one of the principal working languages in ASEAN nations, necessitating that ASEAN students complete an English test from graduation.  This mandate would positively influence education, tourism, commerce, and investment in ASEAN regions. The present study was to measure the effect of the TOEFL preparation program on the English language proficiency of Islamic economics and business students in Indonesia. Using one group pre-test and post-test design, an experimental group consisting of 20 students was randomly selected from 50 students majoring in various Islamic economic and business programs in the first year. The experimental group were intensively taught and learned TOEFL preparation materials using a wide range of teaching and learning strategies and activities. Their ability was measured prior to and after the teaching intervention. The results of statistical measurement using t-test indicate a significant difference between the students mean score of both the pre-test and the post-test. Thus, this one group pre-test and post-test study served as an experiment to enhance students’ English language proficiency, particularly their listening, reading, and grammar mastery, respectively. The findings of the present study provide new insights for teachers and educational institutions in developing effective TOEFL preparation programs to improve students' English skills in various educational institutions.